Japanese encephalitis virus infection induces mitochondrial-mediated apoptosis through the proapoptotic protein BAX - Yang, Ke; Li, Xinran; Yang, Shuqing; Zheng, Yi; Cao, Sanjie; Yan, Qigui; Huang, Xiaobo; Wen, Yiping; Zhao, Qin; Du, Senyan; Lang, Yifei; Zhao, Shan; et al. (Frontiers in Microbiology, 2024)
The Japanese encephalitis virus (JEV), a zoonotic flavivirus, is Asia’s primary cause of viral encephalitis. JEV induces apoptosis in a variety of cells; however, the precise mechanisms underlying this apoptosis resulting from JEV infection remain to be elucidated. Our previous studies showed that the proapoptosis gene BAX may have a role in JEV proliferation. In this study, we constructed a PK-15 cell line (BAX.KO) with a knockout of the BAX gene using CRISPR/Cas9. The knockout of the BAX gene effectively inhibited the proliferation of JEV, resulting in a 39.9% decrease in viral protein levels, while BAX overexpression produced the opposite effect. We confirmed that JEV induces apoptosis of PK-15 using 4′,6-diamidino-2-phenylindole (DAPI) staining and Annexin V-FITC/PI staining. Furthermore, we found that the phosphorylation of P53 and the expression levels of BAX, NOXA, PUMA, and cleaved-caspase-3/9 were significantly upregulated after JEV infection. Moreover, we found that JEV infection not only caused mitochondrial damage, the release of mitochondrial cytochrome C (Cyt C), and the downregulation of the apoptosis-inhibiting protein BCL-2 but also reduced the mitochondrial membrane potential (MOMP) and the accumulation of intracellular reactive oxygen species (ROS). These factors collectively encourage the activation of the mitochondrial apoptosis pathway. In contrast, BAX gene knockout significantly reduces the apoptotic changes caused by JEV infection. Treatment with the caspase3 inhibitor attenuated JEV-induced viral proliferation and release, leading to a decrease in viral protein levels of 46% in PK-15 cells and 30% in BAX.KO cells. In conclusion, this study clarified the molecular mechanisms of JEV-induced apoptosis and provided a theoretical basis for revealing the pathogenic mechanisms of JEV infection.